Hydrodynamics of multi-sized particles in stable regime of a swirling bed - Miin, C.S. (Springer New York LLC, 2015)
Using particle imaging velocimetry (PIV), we observed particle motion within the stable operating regime of a swirling fluidized bed with an annular blade distributor. This paper presents velocity profiles of particle flow in an effort to determine effects from blade angle, particle size and shape and bed weight on characteristics of a swirling fluidized bed. Generally, particle velocity increased with airflow rate and shallow bed height, but decreased with bed weight. A 3Â° increase in blade angle reduced particle velocity by approximately 18. In addition, particle shape, size and bed weight affected various characteristics of the swirling regime. Swirling began soon after incipience in the form of a supra-linear curve, which is the characteristic of a swirling regime. The relationship between particle and gas velocities enabled us to predict heat and mass transfer rates between gas and particles. Â© 2015, Korean Institute of Chemical Engineers, Seoul, Korea.